Reestructuración de la Comisión de Gestión de los recursos propios, y actividades productivas y empresariales de las instituciones educativas de la Policía Nacional del Perú (PNP) - Quiñe Zavaleta, Victor Hugo (2023)
The present research contains the proposal of Innovation on a prototype of Project for the "Restructuring of the management commission of own resources and productive and entrepreneurial activities of the PNP educational institutions" facing the ineffective administrative management in the PNP educational institutions in Lima during the period 2017-2018, whose objective is to answer the question In what way the Administrative Management has been ineffective in the PNP Educational Institutions in the Lima Region, during the period 2017 - 2018? From the approach of Education, the methodology of analysis has been developed structurally carrying out the research, through the evidence described and explained, applying the statistical operational method of descriptive analysis, complying with the methodological process of research for the survey of the administrative part, parents and teachers, whose result will facilitate the existence of the facts enunciated through the study. Concluding the research process through the descriptive method and explanations, it has been described in detail with evidence and the systematization of data from the method that the commissions of Management of own resources, and productive and entrepreneurial activities of the educational institutions of the National Police of Peru have demonstrated an inefficient administration of economic resources by those responsible, generating a situation of social conflict among the actors of the educational institutions of the PNP.